2020
DOI: 10.1253/circj.cj-20-0407
|View full text |Cite
|
Sign up to set email alerts
|

Extended Sedentary Time Increases the Risk of All-Cause Death and New Cardiovascular Events in Patients With Diabetic Kidney Disease

Abstract: Background: Sedentary behavior may be an independent risk factor for cardiovascular events. This study aimed to clarify the effects of extended sedentary time in patients with diabetic kidney disease (DKD) on the risk of all-cause death and new events. Methods and Results:A prospective cohort study was performed over 39 months. The study included 173 patients with DKD who completed the International Physical Activity Questionnaire (IPAQ) (101 men; mean age, 71±11 years); 37 patients (21.4%) were diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…23 In addition, among nondialysis patients with CKD, extended sedentary time was associated with risk of all-cause and CVD-related mortality. 24,25 These studies reported a linear association between sedentary time and mortality risk, which was questionable. A systematic review demonstrated a nonlinear association between total sitting time and all-cause mortality in general population, with a threshold identified at 3-4 hours per day of TV viewing, above which the risk was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition, among nondialysis patients with CKD, extended sedentary time was associated with risk of all-cause and CVD-related mortality. 24,25 These studies reported a linear association between sedentary time and mortality risk, which was questionable. A systematic review demonstrated a nonlinear association between total sitting time and all-cause mortality in general population, with a threshold identified at 3-4 hours per day of TV viewing, above which the risk was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that, according to the literature review, there are no reports focusing directly on the analysis of physical activity using IPAQ in the context of VR utilization among haemodialysis patients. Studies conducted in haemodialysis patient groups used IPAQ only to determine the relationship between the level of physical activity and the occurrence of sarcopenia [28], cognitive abilities [29], depression [30], cardiovascular disorders [31], and to compare the short version of the IPAQ with accelerometer-based physical activity measurement in haemodialysis patients [32], as well as to assess the plasma levels of 25-hydroxyvitamin D compared to the level of physical activity [33].…”
Section: Discussionmentioning
confidence: 99%
“…Living an inactive and sedentary life has been associated with worse cardiovascular outcomes and mortality in kidney disease patients both dependant on dialysis and those who are not, with ameliorations in outcomes in subjects being more active. 5,[42][43][44] Physical exercise has considerable effects on vascular function both at acute and chronic stages through various mechanisms. The beneficial effects of exercise on vascular health include improvement in serum lipid profile and blood pressure, nonetheless, it is not limited to such alterations.…”
Section: Vascular Functionmentioning
confidence: 99%
“…Living an inactive and sedentary life has been associated with worse cardiovascular outcomes and mortality in kidney disease patients both dependant on dialysis and those who are not, with ameliorations in outcomes in subjects being more active 5,42–44 …”
Section: The Pathophysiological Perspectivementioning
confidence: 99%